The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/jcp.30589
|View full text |Cite
|
Sign up to set email alerts
|

The PRMT5/HURP axis retards Golgi repositioning by stabilizing acetyl‐tubulin and Golgi apparatus during cell migration

Abstract: The Golgi apparatus (GA) translocates to the cell leading end during directional migration, thereby determining cell polarity and transporting essential factors to the migration apparatus. The study provides mechanistic insights into how GA repositioning (GR) is regulated. We show that the methyltransferase PRMT5 methylates the microtubule regulator HURP at R122. The HURP methylation mimicking mutant 122F impairs GR and cell migration. Mechanistic studies revealed that HURP 122F or endogenous methylated HURP, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 61 publications
(83 reference statements)
2
10
0
Order By: Relevance
“…To investigate the mechanisms by which JMJD6 regulates GR and cell migration, we noticed that JMJD6 is reported to act against PRMT5 by demethylating the substrates of PRMT5, and our previous works show that PRMT5 methylates HURP at R122 (Chiu et al, 2022). Therefore, we firstly tested the interaction of JMJD6 and HURP by performing immune‐coprecipitation and found that JMJD6 interacted with HURP, no matter exogenous or endogenous version of JMJD6 and HURP (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To investigate the mechanisms by which JMJD6 regulates GR and cell migration, we noticed that JMJD6 is reported to act against PRMT5 by demethylating the substrates of PRMT5, and our previous works show that PRMT5 methylates HURP at R122 (Chiu et al, 2022). Therefore, we firstly tested the interaction of JMJD6 and HURP by performing immune‐coprecipitation and found that JMJD6 interacted with HURP, no matter exogenous or endogenous version of JMJD6 and HURP (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…The following antibodies, plasmids and reagents used in the study were listed below with working dilution or concentration, catalog number, and manufactory company: actin antibody (Western blot, WB ‐ 1:1000, sc8432, Santa cruz), α‐tubulin antibody (WB—1:1000; sc‐5286; Santa cruz), γ‐tubulin antibody (Immunofluorescence; IF—1:100; sc‐17788; Santa cruz), Cdc42 antibody (WB—1:1000; sc‐87; Santa cruz), GFP antibody (WB—1:2000; 11814460001; Roche), GRASP65 antibody (IF—1:1000; ab174834; Abcam), HA antibody (WB—1:2000; H3553; Sigma), HURP, HURP m122, and HURP nm122 antibody (Chiu et al, 2022), JMJD6 antibody (WB ‐ 1:500, sc‐32740, Santa cruz), NF‐кB antibody (IF ‐ 1:100, sc‐8008, Santa cruz), V5 antibody (WB ‐ 1:2000, GTX628592, Gene Tex), PADI4 antibody (WB—1:1000; #32493; Signalway), SAS6 antibody (WB—1:1000; sc376836; Santa Cruz), p EGFP (#13031; addgene), EGFP‐HURP WT, 122 K,122 F (Chiu et al, 2022), V5‐JMJD6 (B. Chang et al, 2007), p NF‐кB ‐Luc reporter plasmid (Chen et al, 2015), HA‐HURP (Yu et al, 2005), BFA (1 μg/ml; B6542, Sigma), ARF6 inhibitor SecinH3 (25 μM; CAS 853625‐60‐2; Santa Cruz), Cdc42 inhibitor ML141 (25 μM; SML0407; Sigma), NF‐кB inhibitor IV (50 μM; 481412; MERCK), PMA (1 μg/ml; P1585; Sigma), puromycin (2 μg/ml; ant‐pr‐5b; Invivogen). 293T and HeLa were from ATCC.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations